2019
DOI: 10.1002/ejic.201900952
|View full text |Cite
|
Sign up to set email alerts
|

Actinide Endohedral and Exohedral Cubic Siloxanes: An(IV)@(HSiO1.5)8 and An(IV)&(RSiO1.5)8 (An = U, Np, Pu; R = H, Cl, OH)

Abstract: Actinide metallasilsesquioxanes and their distinctive bonding properties have received an increased attention due to their potential value in advanced nuclear science and biomedicine. Herein, we have proposed a new class of endohedral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…13 Recently, a series of actinide (uranium, neptunium, and plutonium) metallasilsesquioxanes were theoretically predicted, showing a prospect for the disposal of radioactive actinides. 14 The most popular synthetic approaches to cagelike metallasilsesquioxanes include the "synthon method" with hexameric Si 6 15a,b and heptameric Si 7 , 15c−e cyclic Si 4 , 15f or individual 15g,h silanols as starting reagents. An alternative approach implies a self-assembly with RSi(O)O − siloxanolate 15i,j units.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13 Recently, a series of actinide (uranium, neptunium, and plutonium) metallasilsesquioxanes were theoretically predicted, showing a prospect for the disposal of radioactive actinides. 14 The most popular synthetic approaches to cagelike metallasilsesquioxanes include the "synthon method" with hexameric Si 6 15a,b and heptameric Si 7 , 15c−e cyclic Si 4 , 15f or individual 15g,h silanols as starting reagents. An alternative approach implies a self-assembly with RSi(O)O − siloxanolate 15i,j units.…”
Section: ■ Introductionmentioning
confidence: 99%
“…29 By design, partly condensed polyhedral silsesquioxanes can be also regarded as versatile ligands for the construction of various cagelike metallacomplexes. 30−38 These intriguing compounds attract significant interest for the potential removal of radioactive elements, 39 fabrication of flame retardants, 40−45 biomedical agents, 46 luminescent materials, 47,48 or molecular magnets. 49 Magnetic studies revealed rare cases of singlemolecule magnets (SMMs), 48,50 spin glass, 51 or spin−flip transition 52 effects.…”
Section: ■ Introductionmentioning
confidence: 99%